Developing a framework for English language curriculum evaluation in Oman / Khalid Salim Saif Al-Jardani - Al-Jardani, Khalid Salim Saif (2013)
The research studies the ELT context and the Curriculum Evaluation area in Oman. This study identifies the need for developing a framework for the Curriculum Evaluation, and then develops and tests it in the Omani context in order to develop a modified version of the framework. The study utilizes a developmental research as a framework for Curriculum Evaluation and it has three phases. It starts with the need for developing the framework for Curriculum Evaluation by involving 7 samples of curriculum officers The second phase comprises of using the Delphi methods with three rounds involving 12 samples of curriculum evaluation experts to develop the framework. The final phase of the study includes 34 samples of -English supervisors and Ministry officers to constitute a framework evaluation. The research highlighted the need for English Language Curriculum Evaluation Framework. These findings were supported by all participants. It also stipulated a list of elements. This doctoral research also found that these particular elements are useful for the Omani context, however continuous development should be underscored. This can complement the selected elements and form a good basis for any other framework within Oman.